2021
DOI: 10.1007/s10792-021-01969-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of capsular tension ring on optical and multifunctional lens position outcomes: a systematic review and a meta-analysis

Abstract: AIM: To evaluate the effect of capsular tension rings with multifunctional lens position and optical outcomes. METHODS: We de ned multifunctional lens more than improve vision, but also restore visual quality. Search of PubMed, EMBASE, Cochrane Library. Scopus for English-language articles published up to November 11, 2020. Randomized controlled trials and comparative prospective clinical trials were selected. Data extraction was completed by independent pairs of reviewers. Risk of bias was evaluated using the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…6 In eyes without the risk of zonular instability, however, the effects of CTR on refractive results of multifocal IOL implantation remain inconclusive. 7 Although some studies demonstrated the beneficial effects of CTR implantation on the refractive outcomes after multifocal IOL implantation, others reported that the coimplantation of CTR and multifocal IOL had no statistically significant impact on refractive stability. [8][9][10][11][12][13] These studies were conducted using a manual capsulotomy technique in 2 separate study groups consisting of different individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In eyes without the risk of zonular instability, however, the effects of CTR on refractive results of multifocal IOL implantation remain inconclusive. 7 Although some studies demonstrated the beneficial effects of CTR implantation on the refractive outcomes after multifocal IOL implantation, others reported that the coimplantation of CTR and multifocal IOL had no statistically significant impact on refractive stability. [8][9][10][11][12][13] These studies were conducted using a manual capsulotomy technique in 2 separate study groups consisting of different individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The study results obtained in eyes without risks of zonular instability were inclusive. 7 Alió et al indicated that combined use of CTR and plate haptic bifocal IOLs provided better IOL stability, resulting in good efficacy, predictability, and safety and increased intraocular optical performance after surgery. 8,9 Mastropasqua et al demonstrated that implantation of CTR with multifocal IOL reduced the ocular wavefront error related to a reduction of third-order aberration associated with a better IOL position.…”
Section: Discussionmentioning
confidence: 99%
“…Sutured haptic IOLs would also resist late IOL-capsular bag dislocation that pose a risk to standard CTR co-implantation. Considering the significant complication such as extension of a zonular dialysis, violation of the capsular bag, displacement of the CTR into the vitreous, misplacement into the sulcus, or the anterior chamber which might occur during CTR implanatation, this novel technique can be an alternative choice for eyes with zonular insufficiency [17,[23][24][25][26] .…”
Section: Resultsmentioning
confidence: 99%
“…When using CTR, if the zonulopathy is a non-progressive zonulopathy, such as traumatic or iatrogenic zonular dialysis, these cases are well suited for standard CTR, as the remaining zonules are typically of normal tension. In cases of progressive or advanced zonulopathy, such as advanced pseudoexfoliation syndrome, a standard CTR is unlikely to provide the capsular support needed, and will most likely allow the IOL to dislocate postoperatively [24][25][26] . The modified Cionni CTR can prevent the late IOL-capsular bag dislocation, but this Cionni CTR needs scleral fixation, too.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Clinical data to support these properties is limited. 12,13 Understanding the forces acting on the zonules in the presence of zonular weakness can help understand the pathogenesis of the late dropped IOL-bag complex and provide information for the development of improved CTRs and IOLs.…”
Section: Introductionmentioning
confidence: 99%